The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21608/ejabf.2020.95750
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Studies on Water Quality, Plankton and Bacterial Community in Mariout Lake, Egypt

Abstract: Water quality is a highly imperative component to understand the healthiness of a water body and it is a critical factor affecting human health and welfare (Al-Gahwari, 2007). Studies showed that approximately 3.1% of deaths (1.7 million) and 3.7% of disability-adjusted-life-years (DALYs) (54.2 million) worldwide are attributable to unsafe water, poor sanitation and hygiene (WHO, 2005). Globally, the water quality of inland Lakes is of great importance, particularly in countries of the arid region. This makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
6
2
0
Order By: Relevance
“…As is known, fish act as reservoirs of V. cholerae [ 37 ], in which the bacterial form and number differ according to season, fish species, and natural habitat [ 38 ]. For Tilapia niloticus , our results agreed with those of Farouk [ 39 ], who reported a higher value of cholerae in examined sediment and water samples as compared with tilapia organs. However, at the time of harvest, fish carry a high microbial load on the surface of their skins, intestinal tracts, and gills, which might pose a public health risk after faulty handling, processing, or cooking by consumers, thereby acting as a potential vector.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As is known, fish act as reservoirs of V. cholerae [ 37 ], in which the bacterial form and number differ according to season, fish species, and natural habitat [ 38 ]. For Tilapia niloticus , our results agreed with those of Farouk [ 39 ], who reported a higher value of cholerae in examined sediment and water samples as compared with tilapia organs. However, at the time of harvest, fish carry a high microbial load on the surface of their skins, intestinal tracts, and gills, which might pose a public health risk after faulty handling, processing, or cooking by consumers, thereby acting as a potential vector.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to crustacean fish, researchers have found a state of mutualism between the fish and the bacteria, in which V. cholera secrete many extracellular proteins as chitinase and protease, which in turn help the inhabited fish digest the proteins and chitin of the prey’s exoskeleton [ 16 , 39 , 41 ]. Therefore, it makes sense that crustacean seafood and copepods act as major reservoirs of V. cholerae within the aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…(6), the annual average of water salinity ranged between 3.35 and 5.65 ‰, in (Main Basin) and (Fish Farm), respectively. Similar results mentioned by Farouk et al (2020) who reported that the values of TDS, EC and salinity were higher in (basin 1000) than other basins. The Alkalinity may be defined as the excess of anions weak acids in seawater.…”
Section: Water Salinitysupporting
confidence: 87%
“…Chlorophyll "a" values which recorded alongside the study were between 47.6 µg/l during autumn and 459.6 µg/l during spring in (Main Basin at site 2) and (Northwest Basin at site 2), respectively. Similar result mentioned by Farouk et al (2020) who revealed that, maximum values of chlorophyll "a" were recorded during spring season of the study which may be related to increase phytoplankton with increase nutrients of TN and TP. Fig.…”
Section: Chlorophyll "A"supporting
confidence: 87%
See 1 more Smart Citation